Synthesis and Characterization of Trihydro mono and Dihydrobis(indole-3- acetic acid)Borate Ligands and Some of Their Metal Complexes - Noori Khaleel, Asmaa Mohammed (Iraqi Journal of Science, 2023)
Two new ligands Na2[ H3B (BDIA)].0.05H2O (L1)(BDIA = 1-Boranyl-2,3-Dihydro-1H-Indol-3-yl)]Acetic Acid and Na3[H2B(BDIA)2].0.3H2O.0.3CH3Ph (L2)were synthesized by reaction of NaBH4 with indole -3- acetic acid (IAA) . Thecoordination properties of ligands were studied with Co(II) , Ni(II) , Cu(II) andPt(IV) ions. Characterization and structural aspects of the prepared compounds wereelucidated by 1HNMR, FTIR electronic spectra, magnetic susceptibility, elementaland metal analysis, thermal analysis (TG & DTG) and conductivity measurements.The obtained data for metal complexes suggested square planar geometry forcopper complexes, octahedral geometry for nickel and platinium complexes andtetrahedral geometry for cobalt complex. The analytical data confirmed that theligands were coordinated to the metals via oxygen atom of carboxylate groups andby agostic hydrogen of borate (B-H M agostic interaction).